Alluvial plain morphostratigraphy affected by recent mud and debris flows: a study in the Jacareí River basin (southern coast of Brazil) - Paz, Otacílio Lopes de Souza da; Paula, Eduardo Vedor de (Revista Brasileira de Geomorfologia, 2022)
Sedimentary records are important to understand the evolution of river systems. Morphostratigraphic studies associate sedimentary records with landforms. Mud and debris flows, common in the Serra do Mar mountain range, have a marked impact on the morphostratigraphy of adjacent alluvial plains. The objective of this study was to analyze morphostratigraphic units in an alluvial plain affected by recent mud and debris flows. The study area was the Jacareí River alluvial plain (coast of Paraná State, Brazil) which was hit by extreme gravitational events in March 2011. Geospatial and field survey data were analyzed in a GIS environment to produce a morphostratigraphic map. Units were identified in three contexts: formed earlier than 2011, formed by the 2011 mud and debris flows, and formed after 2011. The deposits instantly formed in 2011 present rocks and pebbles (debris flows) and massive sandy facies (mud flows), with a thickness of between 0.5 and 1 meter. They are easily identified due to abrupt changes in particle size, color, presence of roots, and quantity of organic matter. The results shed light on the evolutionary processes at work in the Jacareí River coastal plain landscape, with the 2011 event representing a phase of the sedimentary cycle of alluvial plains along the Serra do Mar mountain range.